EFISIENSI PEMAKAIAN ENERGI LISTRIK PADA ESKALATOR MENGGUNAKAN INVERTER DI MALL SARINAH THAMRIN - Suherman Suherman; Dewi Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
An escalator or moving staircase is a type of vertical transportation that uses a conveyor system to move people up and down. This research is motivated by the fact that many people do not know the energy used by escalators when moving fast and slow, and are not aware that they can save energy by using more efficient technology, the technology is called an inverter. This study examines how well escalators use electrical energy and what factors affect their work efficiency. The test results show that an induction motor at a frequency of 20 Hz has an efficiency of 0.9% and a slip value of 1.6%, then at a frequency of 50 Hz it has an efficiency of 0.7% and a slip value of 3.3%. The electricity cost of an induction motor at a frequency of 20 Hz is Rp 140,855.28, then at an induction motor with a frequency of 50 Hz is Rp 150,537. So the results of this study can be concluded that the use of Inverter technology can affect how much energy an escalator uses and its electricity costs. The use of inverter technology can reduce the electrical power used during low-traffic times, which helps save electricity costs.